The infrastructure of the Romanian financial system in the current crisis - IONESCU, Eduard; OPREA, Cristian (Annals of Spiru Haret University. Economic Series, 2012)
International macroeconomic an financial environment is subjected to tension but remains relatively strong, even if is a visible slowdown in economic growth in some countries, it materializes the asset price correlation due perceptions adjustment regarding risk, and financial market characteristics changes significantly. Systemically important components in the financial system architecture are represented by the payment and settlement system for financial instruments. These systems, from their implementation until now, did not faced particular problems because of high standards observance in terms of safety and operational efficiency and the measures taken by the central bank.